FIGHTING MONEY LAUNDERING AND CORRUPTION: FINANCIAL AND ECONOMIC ASPECTS - A. I. Selivanov (Финансы: теория и практика, 2017)
The Russian Federation has a consistent policy to combat money laundering and corruption. The fight against these negative phenomena requires further improvement of the regulatory, supervisory and monitoring and law enforcement efforts as well as focused activities of the government bodies in the financial and economic sphere through the formulation and joint implementation of special measures in this area.The article uses an integrated approach, system analysis, analysis of research results of a wide range of domestic and foreign works, synthesis of managerial decisions.The paper outlines causes and conditions underlying money laundering and corruption and proposes targeted economic and financial measures to prevent and combat these phenomena. The author points out that specific management and organizational measures based on the proposed approach should be worked out and applied.